Phygital in games: a systematic review of trends, characteristics, the user experience, technologies, and tools - Nurasilah Osman; Nadia Akma Ahmad Zaki; Tengku Siti Meriam Tengku Wook; Maizatul Hayati Mohamad Yatim; Nor Masharah Husain; Norly Jamil (International Journal of Evaluation and Research in Education (IJERE), 2026)
In the 21st century, the evolution of phygital technology has transformed various sectors, including retail, marketing, heritage, education, edutainment, and gaming. However, phygital interfaces are dynamic, continuously evolving alongside technological advancements and user expectations. This study aims to identify trends, characteristics, user experiences, and the tools or technologies used in phygital gaming. A systematic literature review (SLR) was conducted using the preferred reporting items for systematic reviews and meta-analysis (PRISMA) framework, analyzing 26 publications from Web of Science (WoS), Scopus, and IEEE Xplore. The findings revealed seven key characteristics of phygital interfaces and six positive impacts on user experience. Additionally, various phygital technologies and tools were identified as essential in the education, edutainment, and entertainment contexts of gaming. These technologies enhance engagement, interactivity, and immersion by seamlessly integrating physical and digital elements. Therefore, this study contributes to improving user experiences and expanding knowledge in the context of phygital interfaces. Future research should explore potential challenges in adopting phygital technologies, particularly from educators’ perspectives, to uncover new insights into their implementation and effectiveness.